Sharī’ah and the Politics of Pluralism in Indonesia - Ratno Lukito (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
Keeping in mind the Indonesian Government's policy regarding legal pluralism, this article will take a closer look at how the Government deals with the existence of both Islamic law and customary law (adat). The adoption of